A bilateral decomposition analysis of the impacts of environmental regulation on energy efficiency in China from 2006 to 2018 - Wenfei Song; Xianfeng Han (Energy Strategy Reviews, 2022)
Based on the data set of 30 provinces in China from 2006 to 2018, this paper decomposed the two-sided effects of environmental regulation on energy efficiency and calculated their net effects by using the two-tier stochastic frontier model. First, empirical research shows that environmental regulation has a less inhibiting effect than the promoting effect on energy efficiency, resulting in the net effect a visible positive feature. Second, the inhibition effects contributing to the total variance of energy efficiency only accounted for 0.10%, while the promotion effect was up to 99.90%. Third, the contribution of environmental regulation to energy efficiency has undergone a ‘U-shaped’ process over the period 2006–2018. Fourth, there were significant regional differences in the net effects of environmental regulation on energy efficiency, especially the disparities between the western, central and eastern parts of China. Fifth, environmental regulation has greater driving force on energy efficiency enhancement in regions with high level of regional development. Based on the research conclusions, it is necessary to implement environmental regulation policies address regional differences, adopt the supporting incentive mechanism for regions with good performance, and establish an inter-regional coordination and linkage mechanism for energy efficiency improvement driven by environmental regulation.